The effect of formal and informal communication on managerial satisfaction and performance - Christopher Orpen (Communicare)
128 middle-managers working for 1 different organisations supplied data about their communications with different persons in their organization. From this data measures were developed for each manager of (a the frequency of his scheduled (formal) communications, and (b) the frequency of his unscheduled (informal) communications with superiors (upward communication), with peers (horizontal communication) and with subordinates (downward communication). Significantly positive relations were formed between unscheduled communications and job satisfaction, especially horizontal communication None of the relations between scheduled or unscheduled communications and job performance were significant